Taxonomic corrections and new records in vascular plants of Kyrgyzstan, 5 - Lazkov, Georgy A.; Sennikov, Alexander N. (Memoranda Societatis pro Fauna et Flora Fennica, 2017)
A new series of notes on distribution, taxonomy, morphology and nomenclature of some vascular plants in Kyrgyzstan is collected. A new hybrid, Eremurus ×decoloratus (E. regelii × E. lactiflorus), is described. Corydalis schanginii subsp. ainae is elevated to the species rank as C. ainae and for the first time reported from Kyrgyzstan (Western Tian-Shan: Talas Depression) and Uzbekistan; its distribution is completed and mapped. Several new records are presented as follows. Native species new to Kyrgyzstan: Acantholimon titovii (Boom Ravine), Allium inops Vved. (Western Tian-Shan: Echkili-Too Mts.), Filago hurdwarica (Alay Range), Pedicularis mariae (Ysyk-Köl Depression, Naryn River). Alien species new to Kyrgyzstan: Allium atroviolaceum (Turkestan Range, historical record). New regional records of native species: Corydalis schanginii (Talas Range), Dryopteris mindshelkensis (Western Tian-Shan: Chatkal Range; other records are verified), Melica nutans, Sedum hybridum, Thalictrum sultanabadense (all Western Tian-Shan: Uzun-Akmat Mts.), Nepeta pungens (Moldo-Too Mts.), Pedicularis alberti (Western Tian-Shan: At-Oinok and Uzun-Akmat Mts.), Phlomoides milkoi (Uzun-Akmat Mts.), Picnomon acarna (Western Tian-Shan: Talas Depression). New regional records of alien species: Chenopodium vulvaria (Chatkal Range), Berteroa incana, Galeopsis bifida (both Western Tian-Shan: Suusamyr Range), Galeopsis ladanum (Western Tian-Shan: Fergana Range). The distribution data for Allium dodecadontum, Corydalis ainae and C. schanginii are collected and verified, and the complete distribution areas of these species is mapped for the first time. The distribution of Berteroa incana in Kyrgyzstan is mapped, and the status of its localities (native vs. alien) is identified.